Adam Smith and the Economy of the Passions. - Keppler, Jan Horst (Routledge Studies in the History of Economics, v. 116., 2010)
The fertility of Adam Smith's work stems from a paradoxical structure where the pursuit of economic self-interest and wealth accumulation serve wider social objectives. The incentive for this wealth accumulation comes from a desire for social recognition or "sympathy"--The need to recognise ourselves in our peers -- which is the primary incentive for moderating and transforming our violent and egotistical passions. Adam Smith thus examines in detail the subliminal emotional structure underlying market behaviour. This new book by Professor Jan Horst Keppler presents an Adam Smith fo.